The Savage Organizational Scoring System for the Rey-Osterrieth Complex Figure Test: Norms and New Data From Veterans in a Traumatic Brain Injury Clinic. Issue 6 (December 2021) - Mangum, Ryan W.; Tolle-Fu, Kathryn A.; Hale, Andrew C.; Gradwohl, Brian D.; Spencer, Robert J.
The Rey-Osterrieth Complex Figure Test (RCFT) permits quantifying diverse cognitive abilities, including executive function (EF). We evaluated the psychometric properties of a scoring procedure for the RCFT, the Savage Organizational Scoring System (SOSS), that awards points for drawing the largest structural elements of the figures as continuous wholes. This was a two-phase study: first, we conducted a systematic literature search for studies using the SOSS, and aggregated previously published data for healthy controls to create a normative database; second, we observed performances from veterans evaluated for traumatic brain injury (TBI), examining the reliability of their SOSS scores, the SOSS correlations with two EF measures and the participants' self-reported cognitive functioning, and then compared their mean scores to normative expectations. Across our literature-derived normative database, the aggregated mean SOSS score was 4.12 ( SD  = 1.72), which was marginally higher than that of our veteran participants evaluated for TBI, 3.72 ( SD  = 1.79). The SOSS had modest internal consistency (α = .59). Unlike the criterion EF measures, the SOSS was not significantly related to self-reported cognitive functioning. The SOSS shared a small, significant correlation with Trails B and Shipley Abstraction; but RCFT Copy scores were more strongly related to these tests, and the SOSS added no significant incremental predictive value beyond the RCFT Copy score. However, SOSS scores did predict RCFT Recall beyond RCFT Copy scores. We conclude that the SOSS has modest reliability and is predictive of RCFT Recall scores, but it is not strongly correlated with other EF measures, and it is only minimally affected by mild TBI.